OPTIMALISASI PENGELOLAAN UMKM KERIPIK BAWANG KELURAHAN PULO AMPEL MELALUI PROGRAM KULIAH KERJA MAHASISWA - Ibrohim Ibrohim; M Jaenal Arifin; Fazar Nuruzma; Yulita Isyara Rahmawawi; Syifa Ayyasi (STAI Darul Qalam Tangerang, 2022)
Onion chips are a snack and crunchy texture made from wheat flour base, with the addition of garlic, celery leaves and flavorings. The efforts made after discovering the weaknesses in the development of MSMEs in Pulo Ampel sub-district are providing explanations about product marketing, more attractive packaging, adding flavor variants and maintaining product quality with a target so that wider marketing reaches all levels of society as well as increasing the selling value of products. SWOT analysis is one of the methods used to evaluate strengths, weaknesses, Opportunities and Threats in a Business speculation. From SWOT Analysis to increase the potential and development of onion chip makers in Pulo Ampel Village The steps that must be taken by the makers and the Village government are: 1. Selling and marketing onion chips through online media. 2. The production of onion chips is carried out when there is a cooking from the Buyer. Through this community service activity, it aims to provide assistance to MSME actors, one of which is from the aspects of marketing, product packaging and is an effort that can be developed and can be done to encourage the improvement of MSMEs and drive the economy in Pulo Ampel district